EFFECTIVENESS OF APPLICATION OF TAHFIDZ AND TAKRIR METHODS IN IMPROVING THE MEMORIZATION OF THE AL-QUR'AN OF STUDENTS AT BOARDING SCHOOL ZAWIYATUL HUFFAZH QUR'AN MEMORIZING COTTAGE MEDAN - Ainaya, Tharina; Hasibuan, Muhammad Iqbal; Sabri, Rijal (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2024)
This research is motivated on the basis of an instilling of religious character values which is a way for a person or institution to instill religious character values in students by using a good method. This study aims to determine: (1) how the religious character of the students of SMPIT Al-Munadi Medan, (2) what religious character values are developed at SMPIT AL-Munadi Medan, (3) what supporting factors can increase the religious character of the students of SMPIT AL-Munadi Medan, (4) what are the supporting factors that can improve the religious character of the students of SMPIT AL-Munadi MedanThis research is a field research or field research, with the type of qualitative research. In the research that the author did, the research subjects taken as research sources were the principal, student representatives, teacher staff and students. The data collection technique uses the method of observation, interviews, and documentation.